1982
DOI: 10.2466/pms.1982.55.2.623
|View full text |Cite
|
Sign up to set email alerts
|

Echo Perception of Shape and Texture by Sighted Subjects

Abstract: Experienced blind subjects have previously demonstrated good echo perception of size and distance and some echo-discrimination of shapes and textures. In three experiments untrained sighted subjects also proved able to echo-detect and recognize three simple shapes and to recognize fabric and wooden but not carpet and Plexiglas discs at significantly above chance levels. Some improvement occurred over the first few trials but little thereafter, suggesting that this sort of echo perception requires very little t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 6 publications
0
29
1
Order By: Relevance
“…Not surprisingly then, these participants were unable to successfully use echoes to discern the shape of the objects. This runs contrary to the findings of Hausfeld et al (1982) who found that untrained sighted participants could identify simple shapes using echoes. Although these participants were untrained, they received feedback on every trial and 16 improvements in performance over the first few trials indicates that this feedback was useful.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Not surprisingly then, these participants were unable to successfully use echoes to discern the shape of the objects. This runs contrary to the findings of Hausfeld et al (1982) who found that untrained sighted participants could identify simple shapes using echoes. Although these participants were untrained, they received feedback on every trial and 16 improvements in performance over the first few trials indicates that this feedback was useful.…”
Section: Discussioncontrasting
confidence: 56%
“…In 1967, Rice reported preliminary results of a 2D shape discrimination task which suggested that blind echolocators could distinguish between a circle, square, and triangle, but he never followed-up on these initial observations. Later, Hausfeld, Power, Gorta, and Harris (1982) showed that untrained sighted individuals could learn to discriminate simple shapes using echoes, and that a blind participant performed within the range of these sighted individuals.…”
mentioning
confidence: 99%
“…Non-echolocators, however, both blind and sighted, were unable to make these discriminations at any level above chance. In contrast, Hausfeld, Power, Gorta & Harris (1982) study found that sighted participants could identify significantly above chance which of three simple geometric shapes (circle, triangle or square, with surface areas of approximately 177 cm 2 ) was presented at a distance of 25 cm from their forehead. The participants in that study were not practised echolocators and they performed less accurately in comparison to a blind expert echolocator, but it remains somewhat unclear as to the specific cues that are being used to solve such a task.…”
Section: Discriminating Object Size Shape and Materialsmentioning
confidence: 63%
“…In addition to object shape, there is also evidence that an object's material can be identified through echolocation (Hausfeld et al, 1982;DeLong, Au & Stamper, 2007;Milne, Goodale, Arnott, Kish & Thaler, 2005), as different materials such as carpet or wood reflect different sound frequencies in different quantities. Milne and colleagues (2014) showed that both echolocating experts as well as non-experts were able to reliably identify echoes from synthetic foliage, fleece or a whiteboard, and previous research has shown that participants report using pitch and timbre to identify materials such as wood and carpet (DeLong et al, 2007;Hausfeld et al, 1982).…”
Section: Discriminating Object Size Shape and Materialsmentioning
confidence: 99%
See 1 more Smart Citation